Future changes in precipitation for identified sub‐regions in East Asia using bias‐corrected multi‐RCMs. (27th November 2020) - Park, Changyong; Lee, Gil; Kim, Gayoung; Cha, Dong‐Hyun
Abstract: Water management is a crucial issue in East Asia and is significantly influenced by climate change. Because East Asia's precipitation characteristics are varied and complex, it is necessary to implement the analysis of the future changes in precipitation on an objectively classified, specific sub‐regional level to effectively solve these problems. In this study, sub‐regions were objectively classified according to their precipitation characteristics, based on the present observations in East Asia. Additionally, the bias‐correction technique was applied to the regional climate model (RCM) to yield more reliable future precipitation predictions for the sub‐regions. We obtained the following four key results in this study. (1) The classified sub‐regions corresponded well to the observed annual precipitation distribution and adequately reflected the influence of the summer monsoon. The annual precipitation of the classified sub‐regions exhibited a decreasing trend in arid regions and an increasing trend in humid areas. (2) Because the bias‐corrected RCM was able to simulate annual precipitation reasonably, this technique was applied to future scenarios to analyse future changes in precipitation for each classified sub‐region. (3) Future annual precipitation will increase significantly in the region spanning from the western part of Southern China to the area around the Bohai Sea, while the temporal variations of the climatological daily precipitation indicated that sub‐regions under the influence of the East Asian summer monsoon (EASM) will be predicted an increase in second peaks during the summer. Hence, in the future, the EASM rain belt will be strengthened and its average location will move northward from its present location. (4) Because the high‐intensity extreme precipitation indices are expected to have a more considerable increase in all the classified sub‐regions, there is a need to solidify response measures against disasters that could arise from these changes in the East Asian region. Abstract : The high‐intensity extreme precipitation index is expected to have a greater increase than the low‐intensity extreme precipitation indices for all the classified sub‐regions. Additionally, the temporal variations of the climatological daily precipitation predicted the strengthening and northward movement of the EASM rain belt's average location in the future, which will cause two peaks to appear in the mid‐latitude MCCK sub‐region, as well as a noticeable precipitation increase in the second peaks for the WSEC, WSJP, and WNJP sub‐regions.